Translation, adaptation, validity and reliability of the Instrument for Assessment of Primary Health Care (PCATool) in Brazil: version of health professionals - Hauser, Lisiane (2013)
Objective: to translate and adapt the version of the Primary Care Assessment Tool (PCATool) for health professionals in the Brazilian context and assess its validity and reliability. Methods: we conducted a cross-sectional study with 340 healthcare professionals (physicians and nurses) working in the public primary care services in Porto Alegre. We performed the translation, reverse translation, and adaptation of the instrument to the characteristics of the national health service, as well as to cultural aspects. Factorial validity, internal consistency, and stability over time were assessed. Results: nine factors were retained in the exploratory factorial analysis, explaining approximately 75% of the total variation, highlighting the multi-dimensional nature of the instrument. In terms of internal consistency, Cronbach’s alpha ranged from 0.28 to 0.90. Temporal stability was observed for all attributes except family counseling (p<0.05). Conclusions: the results suggest that the PCATool can be useful in measuring the quality of primary care from the perspective of healthcare professionals, being applicable not only for identification, assessment, and screening of primary care attributes within healthcare services, but also for comparative studies.